Chondronecrosis of the larynx following use of the laryngeal mask airway. (24th October 2014) - Beswick, Daniel M.; Collins, Jeremy; Nekhendzy, Vladimir; Damrose, Edward J.
Abstract : This case describes the development of laryngeal chondronecrosis after use of the laryngeal mask airway (LMA). A 69‐year‐old male with prior laryngeal irradiation underwent total knee replacement with general anesthesia via LMA. Postoperatively, he developed laryngeal chondronecrosis, bilateral vocal fold immobility, and aspiration, necessitating tracheostomy and gastrostomy placement. He improved with hyperbaric oxygen therapy, intravenous antibiotics, and endoscopic repair of a residual fistula. Vocal fold motion returned and he was decannulated. Chondronecrosis of the larynx may occur with the use of the LMA, and caution should be used in patients with a history of prior laryngeal irradiation. Laryngoscope, 125:946–949, 2015